Respuesta :

Answer:

[tex]k=2[/tex]

Step-by-step explanation:

Given:-

[tex]3x-y=2[/tex]----------------(Equation 1)

[tex]2x+8=3y[/tex]-------------(Equation 2)

By solving Equation 1 we get,

[tex]3x-y=2[/tex]

[tex]y=3x-2[/tex]---------------(Equation 3)

Now substituting equation 3 in equation 2,

[tex]2x+8=3y[/tex]

[tex]2x+8=3\time (3x-2)[/tex]

[tex]2x+8=9x-6[/tex]

[tex]7x=14[/tex]

[tex]x=2[/tex]---------------(Equation 4)

Now substituting equation 4 in equation 3 we get,

[tex]y=3x-2[/tex]

[tex]y=(3\times 2)-2[/tex]

[tex]y=6-2[/tex]

[tex]y=4[/tex]--------------(Equation 5)

Now,

[tex]y=kx[/tex]

[tex]k=\frac{y}{x}[/tex]

[tex]k=\frac{4}{2}[/tex]

[tex]k=2[/tex]

Therefore [tex]k=2[/tex]

ACCESS MORE